Angiographic CT for intraprocedural monitoring of complex neuroendovascular procedures - Pfaff, Johannes Alex Rolf; Struffert, Tobias; Gölitz, Philipp; Dörfler, Arnd (American Journal of Neuroradiology, 2013)
Evolving techniques in interventional neuroradiology have widened therapeutic options, allowing treatment even in complex cases. Complex neuroendovascular procedures (eg, stent-assisted coiling, stent placement in X- or Y-techniques) require precise delineation of cerebral vasculature and devices. However, because of the complex anatomy or if an ideal projection is not possible, visualization of the parent artery might be difficult. We present 2 complex cases of basilar tip aneurysm in which ACT proved to be beneficial in the intraprocedural monitoring of stent-assisted coil embolization.
CRIS-Team Scopus Importer:2022-08-05